Heightened sensitivity to emotional expressions in generalised anxiety disorder, compared to social anxiety disorder, and controls. Issue 1 (2nd January 2017) - Bui, Eric; Anderson, Eric; Goetter, Elizabeth M.; Campbell, Allison A.; Fischer, Laura E.; Barrett, Lisa Feldman; Simon, Naomi M.
ABSTRACT: Few studies have examined potential differences between social anxiety disorder (SAD) and generalised anxiety disorder (GAD) in the sensitivity to detect emotional expressions. The present study aims to compare the detection of emotional expressions in SAD and GAD. Participants with a primary diagnosis of GAD ( n  = 46), SAD ( n  = 70), and controls ( n  = 118) completed a morph movies task. The task presented faces expressing increasing degrees of emotional intensity, slowly changing from a neutral to a full-intensity happy, sad, or angry expressions. Participants used a slide bar to view the movie frames from left to right, and to stop at the first frame where they perceived an emotion. The frame selected thus indicated the intensity of emotion required to identify the facial expression. Participants with GAD detected the onset of facial emotions at lower intensity of emotion than participants with SAD ( p  = 0.002) and controls ( p  = 0.039). In a multiple regression analysis controlling for age, race, and depressive symptom severity, lower frame at which the emotion was detected was independently associated and GAD diagnosis ( B  = –5.73, SE = 1.74, p  < 0.01). Our findings suggest that individuals with GAD exhibit enhanced detection of facial emotions compared to those with SAD or controls.